An updated systematic review and meta-analysis of the efficacy and safety of early oral feeding vs. traditional oral feeding after gastric cancer surgery - Xu, Dong; Li, Junping; Liu, Jinchao; Wang, Pingjiang; Dou, Jianjian (Frontiers in Oncology, 2024)
Early oral feeding (EOF) has been showed to improve postoperative recovery for many surgeries. However, surgeons are still skeptical about EOF after gastric cancer surgery due to possible side effects. An updated systematic review and meta-analysis aimed to investigate the efficacy and safety of EOF in patients after gastric cancer surgery.Methods: Randomized controlled trials (RCTs) investigating EOF in patients after gastric cancer surgery were searched in the databases of Pubmed, Embase, Clinicaltrials.gov and Cochrane from 2005 to 2023 and an updated meta-analysis was performed using RevMan 5.4 software.The results of 11 RCTs involving 1352 patients were included and scrutinized in this analysis. Hospital days (Weighted Mean difference (WMD) -1.72; 95% confidence interval (CI) -2.14 to -1.30; P<0.00001), the time to first flatus (WMD -0.72; 95% CI -0.99 to -0.46; P<0.00001) and hospital costs (WMD -3.78; 95% CI -4.50 to -3.05; P<0.00001) were significantly decreased in the EOF group. Oral feeding tolerance (risk ratio (RR) 1.00; 95% CI 0.95 to 1.04; P=0.85), readmission rates (RR 1.28; 95% CI 0.50 to 3.28; P=0.61), postoperative complications (RR 1.02; 95% CI 0.81 to 1.29; P=0.84), anastomotic leakage (RR 0.83; 95% CI 0.25 to 2.78; P=0.76) and pulmonary infection (RR 0.65; 95% CI 0.31 to 1.39; P=0.27) were not significantly statistical between two groups.This meta-analysis reveals that EOF could reduce hospital days, the time to first flatus and hospital costs, but it was not associated with oral feeding tolerance, readmission rates or postoperative complications especially anastomotic leakage and pulmonary infection, regardless of whether laparoscopic or open surgery, partial or total gastrectomy, or the timing of EOF initiation.